Assessment of some exotic potato genotypes for their yield performance under Bangladesh condition - Chowdhury, Md Murad Hossan; Islam, Md Amirul; Rahman, Md Habibur; Rahim, Md Abdur; Atikuzzamman, Md; Sathi, Maria Akter (Fundamental and Applied Agriculture, 2019)
A field research was conducted at the Horticulture Farm of Bangladesh Agricultural University, Mymensingh during the period between November 2011 and February 2012 to determine the yield performance of some exotic potato accessions/cultivars. The experiment was laid out in randomized complete block design (RCBD) with three replications. The experiment comprised of six exotic potato accessions viz. AC10064, AC10076, AC10097, AC10109, AC10123 and AC10190, and one cultivar ‘Cardinal’ as control. Data on yield and yield contributing characters were recorded. The lowest days required for plant emergence at accession AC10109 (6.25 d) and the maximum days required at variety Cardinal (10.02 d). The highest tuber length (7.11 cm) and diameter (5.70 cm) were found in the accession AC10109 and lowest length (5.85 cm) and diameter (3.81 cm) of tubers were found in the variety Cardinal. The maximum (274.74 g) and the minimum (130.11 g) yield of tubers hill−1 were found in accession AC10109 and Cardinal, respectively. The maximum yield of tubers was obtained from the accession AC10109 (29.31 t ha−1) closely followed by AC10064 (28.88 t ha−1) and the minimum yield of tubers was obtained from the accession Cardinal followed by AC10190 (15.97 t ha−1). Considering the yield performance, potato accession AC10109 was the best performer followed by AC10064 and performed better than popular existing variety Cardinal. Therefore, these two accessions may be considered for further multi-location trial before final recommendation.